Catalysis with Chalcogen Bonds. Issue 3 (16th December 2016) - Benz, Sebastian; López‐Andarias, Javier; Mareda, Jiri; Sakai, Naomi; Matile, Stefan
Abstract: Herein, we introduce catalysts that operate with chalcogen bonds. Compared to conventional hydrogen bonds, chalcogen bonds are similar in strength but more directional and hydrophobic, thus ideal for precision catalysis in apolar solvents. For the transfer hydrogenation of quinolines and imines, rate enhancements well beyond a factor of 1000 are obtained with chalcogen bonds. Better activities with deeper σ holes and wider bite angles, chloride inhibition and correlation with computed anion binding energies are consistent with operational chalcogen bonds. Comparable to classics, such as 2, 2′‐bipyrroles or 2, 2′‐bipyridines, dithieno[3, 2‐b;2′, 3′‐d]thiophenes (DTTs), particularly their diimides, but also wide‐angle cyclopentadithiazole‐4‐ones are identified as privileged motifs to stabilize transition states in the focal point of the σ holes on their two co‐facial endocyclic sulfur atoms. Abstract : In the focal point : The integration of chalcogen bonds into non‐covalent catalytic systems is realized with deep σ holes and wide bite angles between cofacial endocyclic sulfur atoms of dithieno[3, 2‐b;2′, 3′‐d]thiophenes (DTTs), ready to activate hydride acceptors for transfer hydrogenation of quinolines and imines by lone‐pair recognition in the transition state.